PENERAPAN MODEL TALKING STICK UNTUK MENINGKATKAN PEMBELAJARAN IPS SISWA KELAS V SDN PANDANWANGI 4 KECAMATAN BLIMBING KOTA MALANG - Wenda, Dhian Dwi Nur; Sasmoko, Heppi (Universitas Nusantara PGRI Kediri, 2015)
It was found that a problem about learning of Social science in the fifth grade of Pandanwangi 4 Elementary school in Malang city which was still conventional. It had an effect on the lowness of activity and the result of students’ learning on a social science lesson. This research was aimed to describe the application of Talking stick model, and the result of students’ learning after talking stick was applied. This research used class action research which was done by using two cycles and the subject of this research was the fifth grade of Pandanwangi 4 Elementary School Malang. The result of this research showed that the application of Talking stick model could increase social science learning which had standard competence ‘respecting service and the role of hero in preparing independence of Indonesia’. Pandanwangi 4 Elementary School which located in Blimbing sub-district Malang city. Therefore, it was suggested that the teacher has to apply Talking stick model in social science learning.